Multiple Nocardial Brain Abscesses in a Renal Transplant Recipient: A Case Report - Nepali, Rabin; Shah, Dibya S; Sharma, Mohan R (Journal of Institute of Medicine Nepal, 2021)
Nocardia is a rare but life-threatening opportunistic infection, especially in immunocompromised patients, including renal transplant recipients. It can cause intracranial abscess which has a mortality of more than 30%. So, when a renal transplant recipient presents with central nervous system involvement, nocardial brain abscess must be considered in the differential diagnosis. Here, we report a such case with multiple nocardial brain abscesses. This case highlights the importance of early diagnosis and treatment to get a good clinical outcome.